2011
DOI: 10.1007/s10443-011-9216-9
|View full text |Cite
|
Sign up to set email alerts
|

Damage Assessment of CFRP [90/±45/0] Composite Laminates over Fatigue Cycles

Abstract: The present paper develops a stiffness-based model to characterize the progressive fatigue damage in quasi-isotropic carbon fiber reinforced polymer (CFRP) [90/±45/0] composite laminates with various stacking sequences. The damage model is constructed based on (i) cracking mechanism and damage progress in matrix (Region I), matrix-fiber interface (Region II) and fiber (Region III) and (ii) corresponding stiffness reduction of unidirectional plies of 90°, 0°and angle-ply laminates of ±45°as the number of cycles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Triphasic stages of ratcheting deformation were related to stress cycles, lifespan, mechanical properties and amplitude and mean stress components by means of linear and logarithmic functions. Mathematical description for such triphasic response has been developed based on earlier research work by authors 23,24 …”
Section: The Ratcheting Strain Formulationmentioning
confidence: 99%
“…Triphasic stages of ratcheting deformation were related to stress cycles, lifespan, mechanical properties and amplitude and mean stress components by means of linear and logarithmic functions. Mathematical description for such triphasic response has been developed based on earlier research work by authors 23,24 …”
Section: The Ratcheting Strain Formulationmentioning
confidence: 99%
“…[1][2][3] The customizable laminate structure provides brilliant mechanical properties for diverse application scenarios by changing the stacking sequence and related fiber orientation. Ahmadzadeh et al [4] developed a stiffness-based model to characterize the progressive fatigue damage in quasi-isotropic carbon fiber-reinforced polymer (CFRP) [90/±45/0] composite laminates with various stacking sequences. Tae et al [5] investigated the fatigue characteristics of the [±θ/0 8 ] S laminate bolted joint with respect to the angle θ and the bolt clamping pressure and compared with the result of the [0 2 / ±45 3 /90 2 ] S laminate.…”
Section: Introductionmentioning
confidence: 99%
“…The static and fatigue 3-point bending tests were implemented on a 3D printed sandwich composites with a re-entrant honeycomb core to evaluate the durability and the ability of this material to dissipate energy [17]. Ramakrishnan et al [18] proposed a fatigue damage mathematical model based on stiffness degradation, which thoroughly considered the mechanical properties of the component materials and various influencing factors; Varvani-Farahani et al [19,20] introduced the influence of ply angle and average stress on composite material fatigue damage into the model proposed by Ramakrishnan et al and Pertuz et al [21] studied tensile and fatigue tests of CFRTPCs and the results showed that carbon fiber isotropic layers had the higher ultimate tensile stress, with 165 MPa. And specimens with nylon matrix, triangular filling pattern and matrix density of 20%, reinforced with carbon fiber at 0-degrees, showed better fatigue performance, increasing significantly the number of cycles before specimen rupture.…”
Section: Introductionmentioning
confidence: 99%